The DKI Jakarta Regional Government Policy to Handling Covid-19 in Basic Services in Health Sector - Marwansyah Marwansyah; Roni Ekha Putera; Aidinil Zetra (Universitas Teuku Umar, 2022)
This study focuses on the policies of the DKI Jakarta Regional Government in handling Covid-19 in the primary health service sector in 2020. The main focus of this research examines the approach that has been taken by the Regional Government in dealing with Covid-19 problems, especially in health service units which are essential services (primary) society needs. Especially DKI Jakarta is the only city in Indonesia with a provincial-level status. This study uses a qualitative method. The form of the DKI Jakarta government's policy efforts in primary health services during the Covid-19 pandemic in 2020 with various tracing efforts by capturing asymptomatic cases in locations at high risk of Covid-19 transmission and treatment (treatment) with measures and solutions to improve; a. Health service capacity; b. Promotive and preventive efforts. Reporting from various references found by researchers, there are two different sides, namely the success and weakness in implementing the policy. The researchers found that promotive and preventive efforts in health service capacity programs were quite reasonable and practical from success. However, on the side of weakness, there are obstacles that the implementation process does not run optimally according to one source. It reflects on the policy perspective. It is expected that DKI Jakarta and other regions to draw valuable lessons for policy administrators.